Mobile Simulator Control System for Isolating Breathing Apparatus of Software-Hardware Platform - Obukhov, Artem; Dedov, Denis; Siukhin, Alexander; Arkhipov, Alexey (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The current problem in the process of training miners is to ensure the mobility and the ability to perform exercises not only on simulators, but also in real conditions of the mine. Therefore, the software and hardware platform of the training complex should include not only imitators of isolating breathing apparatus for developing proper breathing skills in self-rescuers, but also mobile control systems. This will allow carrying out the learning process in conditions similar to real, will increase usability by eliminating wired data transfer interfaces. In addition, the mobile control system of the simulator monitors the trainee’s state indicators in real time in an understandable form for him on a wristband or watch. For the implementation of software and hardware of such system, appropriate structural and functional models were developed, including patterns of interaction between components, data transfer and processing processes. On their basis, a software and hardware implementation of a mobile simulator control system is carried out. The results can be applied in the development of mobile controls in various software and hardware platforms.